(untitled) (Semiárida, 2026)
The xerophytic shrublands of the Monte Phytogeographic Province constitute one of the main vegetation types in the arid-semiarid regions of central Argentina and are subject to recurrent fire disturbances. In these systems, dominated by species of the genus Larrea, post-fire recovery depends primarily on vegetative regrowth and, potentially, on the soil seed bank. However, the role of shrub seeds in these processes has been scarcely studied. The objective was to explore the composition and density of seeds from dominant native shrub species present in the seed bank within communities of Lihué Calel National Park (La Pampa, Argentina) with different fire histories. Additionally, their relationship with vegetation structure was evaluated. Six sites with different fire recurrence patterns were selected (no fires, fires in 2003, 2018, and combinations of events). At each site, vegetation structure and cover were surveyed, and soil samples were collected for analysis of the shrub seed bank. Seeds from five shrub species were identified. Sites with a shorter history of disturbance had a higher proportion of upper shrub layers and higher densities of shrub seeds, whereas sites with recent or recurring fires were dominated by smaller vegetation associated with the regrowth of grasses, subshrubs, and shrubs, along with a marked decrease in seeds in the soil seed bank. No shrub seeds were recorded at the site of the 2018 fire. Furthermore, the highest seed densities were found beneath shrubs, highlighting the importance of these microsites in propagule accumulation. Taken together, the results suggest that increased fire recurrence would promote structural simplification processes and reduce the availability of shrub seeds in the soil, reinforcing the importance of vegetative regrowth as the primary mechanism for persistence and post-fire recovery in these systems.